Three waves of semi-presidential studies. Issue 1 (2nd January 2016) - Elgie, Robert
Abstract : This article reviews the scholarship on semi-presidentialism since the early 1990s. We identify three waves of semi-presidential studies. The first wave focused on the concept of semi-presidentialism, how it should be defined, and what countries should be classified as semi-presidential. The second wave examined the effect of semi-presidential institutions on newly democratized countries. Does semi-presidentialism help or hinder the process of democratic consolidation? The third wave examines the effect of semi-presidential institutions on both recent and consolidated democracies. Third-wave studies have been characterized by three questions: to what extent does the direct election of the president make a difference to outcomes; to what extent does variation in presidential power make a difference; and what other factors interact with presidential power to help to bring about differential outcomes? The article argues that the concept of semi-presidentialism remains taxonomically valid, but that the empirical scholarship on countries with semi-presidential institutions needs to respond to broader developments within the discipline if it is to remain relevant.